Computer Game-Based Learning Media as a Strategy to Increase Students' Motivation Learning - Husni, Mahasin; Sumardjoko, Bambang; Darsinah, Darsinah (At-Taqaddum, 2021)
The success of teaching and learning activities is determined by one of the methods and media of learning. This study aims to determine the needs of learning media, develop learning media based on computer games, and determine the effectiveness of learning media based on computer games on students' motivation and interest in learning. This type of research is Research and Development (R&D), referring to the ADDIE development model. Data collection techniques using observation and questionnaires. The data analysis technique is done by analyzing the questionnaire. The results showed that students needed new learning media with the criteria of using computer technology, game-based, having a colorful display, involving an active role in student participation, easy to operate, equipped with characters, login, and voice access rights. A computer game-based learning media application has been developed called "BEBEB" with a very proper assessment from Media Experts and Material Experts. The effectiveness of the "BEBEB" application as a learning media based on computer games increased learning motivation by 16.5% and interest in learning by 24.33%. The study results indicate that the development of computer-based learning media as a strategy to increase students' motivation and interest in learning at SMK Muhammadiyah 2 Andong Boyolali has been able to be implemented properly. This implies that teachers need to provide learning media that can arouse students' motivation and interest in learning, one of which is using computer game-based learning media.